Growth of selected East Asian economies: the strength of the links to the US and Europe - Tan, Eu Chye; Tang, Chor Foon (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
As East Asian economies have traditionally been associated with export-oriented growth and development, this paper attempts to verify whether there indeed exist direct causal relations between certain East Asian (EA) countries on the one hand and the United States and Europe on the other in terms of the real gross domestic product (GDP). Specifically, their quarterly real gross domestic product (GDP) series spanning from 1999 are subjected to tests for their long run and short run lead-lag relations within a tri-variate modelling framework. Contrary to popular perception, the empirical evidence suggests that generally very nominal links exist between the GDP of these EA countries and that of the US. Direct links with Europe are found to be totally non-existent. All this would imply that the EA economies have a very limited susceptibility to shocks in the US and Europe, unless these shocks precipitate a global economic crisis of severe proportions such as the Great Recession. The growing conviction that when China sneezes, the world would catch a cold is also dispelled by the empirical results
Argument Oeconomica, 2016, Nr 1 (36), s. 105-124
Keywords: causality; cointegration; growth